Hardware implementation of fire detection, control and automatic door unlocking system for automobiles. - Joy Mathavan, J.; Faslan, A.W.; Basith, N.U.A.; Wanigasinghe, W.V.S.D. (International Conference on Trends in Electronics and Informatics (ICOEI 2020), 2020)
During automobile fire accidents, the lives couldn’t be saved because of the failure in opening the vehicle doors. There are systems available for the detection and control of fire accidents in automobiles but those systems are designed to detect the fire, warn the drivers and operate the fire extinguishers to control the fire. The system designed in this research work tends to unlock the vehicle door automatically along with alerting the driver with an alarm and supply fire extinguishers during automobile fire. Temperature sensor and smoke sensor are used to detect the fire and different motors are used to open the door and supply the fire extinguisher. The system works even if the battery fails or the electrical system fails or the door locked manually. Since separate system is installed for each door, in case if the system of a particular door fails, the passenger can be saved by the other door.
Keywords: Automatic door unlock; Accident; automobile; DHT11 temperature sensor; MQ-2 sensor for combustible gas